Manufacturing the Digital Revolution: Building a Sustainable Supply Chain for ICT-Driven Development in India - John Biberman (Columbia University, Earth Institute, Center for Sustainable Development (CSD), 2022)
As adoption of digital technology has accelerated in India, so too has demand for the minerals, hardware components and devices that collectively form the building blocks of the ICT ecosystem. Existing supply constraints are limiting India's ability to build out its digital infrastructure, pointing to an opportunity to expand a sustainable domestic supply chain for these materials. Assembly and fabrication of foreign components can provide easy wins for Indian manufacturing, urged on by high government incentives for Foreign Direct Investment (FDI) in semiconductor manufacturing. Chip fabrication remains an emergent industry within India, but Indian engineers have substantial expertise in designing chips which could be leveraged for domestic manufacturing. India also has substantial mineral resources for battery and semiconductor manufacturing which the nascent industry can take advantage of. Whether manufacturers choose to source raw materials from within India or from locations further afield, the Government of India (GOI) should coordinate with companies to build sustainable legal regimes around mineral extraction which minimize potential for corruption and maximize inclusive local benefits. This effort can go hand-in-hand with India's broader international development priorities, including international applications of Indian platforms for ICT-driven development in fields such as education and health.
Keywords: 330